2019
DOI: 10.1002/jcp.28887
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AC073284.4 suppresses epithelial–mesenchymal transition by sponging miR‐18b‐5p in paclitaxel‐resistant breast cancer cells

Abstract: Breast cancer (BC) is the most prevalent malignant cancer in the world, is the leading cause of cancer-related death female. Recently, there is accumulating evidence that long noncoding RNAs (lncRNAs) might as an important role in the progression of BC.(epithelial-mesenchymal transition (EMT) is considered to play a vital role in tumor cells migration and invasion. Nevertheless, the entire biological mechanisms and functions of lncRNAs in tumor migration, invasion, and EMT remain uncertain. In the present rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…We used the GEO database to select mRNAs that were downregulated in SOC, identified potential lncRNA-miRNA-mRNA interaction networks based on the presence of specific binding sites, and reconstructed a comprehensive ceRNA network. Several recent studies demonstrated that ceRNA-based mechanisms may operate in all types of carcinoma [5,6,[17][18][19][20][21][22][23]. In the present study, among the miRNAs found to be downregulated in SOC, hsa-miR-195-5p and hsa-miR-497-5p were predicted to bind to LINC00284.…”
Section: Discussionsupporting
confidence: 54%
“…We used the GEO database to select mRNAs that were downregulated in SOC, identified potential lncRNA-miRNA-mRNA interaction networks based on the presence of specific binding sites, and reconstructed a comprehensive ceRNA network. Several recent studies demonstrated that ceRNA-based mechanisms may operate in all types of carcinoma [5,6,[17][18][19][20][21][22][23]. In the present study, among the miRNAs found to be downregulated in SOC, hsa-miR-195-5p and hsa-miR-497-5p were predicted to bind to LINC00284.…”
Section: Discussionsupporting
confidence: 54%
“…MiRNA microarray assay revealed that a total of 22 microRNAs were upregulated in GBC-SD cells when PVT1 was knockdown, and we selected miR-18b-5p which was related with the proliferation of GBC cells for further study. MiR-18b-5p has been reported to function as a tumor suppressor and be regulated by lncRNAs 19,20 . By analyzing the sequence of PVT1 and miR-18b-5p, no binding sites were found based on the principle of base pairing, so other mechanisms may exist by which PVT1 inhibited the expression of miR-18b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a group of highly conserved transcripts of >200 nucleotides, with no protein coding ability (6)(7)(8). An increasing number of studies have documented the involvement of lncRNAs in regulating the biological behaviors of cancer cells (9,10). lncRNAs can be categorized as oncogenes and/or tumor suppressors depending on the specific malignancy (11,12), and the aberrant expression of lncRNAs can be used to evaluate the tumorigenesis, progression and relapse of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%